Contributing Factors Of Internet Usage: Southern Region Of Malaysia - Hoon, Kerk Peck (2001)
To date there is no extensive study done on the contributing factors of Internet usage in Southern region of Malaysia. Hence the objective of this study is to complement existing studies by looking at both users and nonusers so that the motivations for and barriers to Internet usage can be identified.